2016
DOI: 10.1111/jon.12327
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Gray Matter Volume in HIV‐Positive Patients with Executive Function Deficits

Abstract: HIV-positive patients with executive functions deficits have reduced volumes of several subcortical structures, primarily in the caudate nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…In some studies, HIV infection has been associated with reduced cortical volume ( Stout et al, 1998 ; Behrman-Lay et al, 2016 ) or with regional cortical thinning ( du Plessis et al, 2016 ; Shin et al, 2017 ; Sanford et al, 2018b ; Sanford et al, 2017 ; Thompson et al, 2005 ). Other studies have found no difference in either cortical volume or thickness associated with HIV infection ( Cole et al, 2018 ; Sanford et al, 2018a ; Corrêa et al, 2016a ; Seilhean et al, 1993 ). A recent meta-analysis found that total gray matter volume was significantly smaller among HIV infected individuals than among non-infected controls, although the standardized mean difference was small (−0.28; O'Connor et al, 2018 ).…”
Section: Introductionmentioning
confidence: 74%
“…In some studies, HIV infection has been associated with reduced cortical volume ( Stout et al, 1998 ; Behrman-Lay et al, 2016 ) or with regional cortical thinning ( du Plessis et al, 2016 ; Shin et al, 2017 ; Sanford et al, 2018b ; Sanford et al, 2017 ; Thompson et al, 2005 ). Other studies have found no difference in either cortical volume or thickness associated with HIV infection ( Cole et al, 2018 ; Sanford et al, 2018a ; Corrêa et al, 2016a ; Seilhean et al, 1993 ). A recent meta-analysis found that total gray matter volume was significantly smaller among HIV infected individuals than among non-infected controls, although the standardized mean difference was small (−0.28; O'Connor et al, 2018 ).…”
Section: Introductionmentioning
confidence: 74%
“…However, given the high prevalence of tobacco use amongst HIV+ patients,(Tesoriero et al, 2010) those in the earlier studies might have been tobacco smokers also. Earlier studies of HIV+ participants found poorer performance on WCST only in those with AIDS compared to the SN controls (Villa et al, 1993), or in those with smaller striatal structures, especially caudate and putamen (Correa et al, 2016), although information regarding the smoking status of these participants were not reported. Since the caudate and putamen have the highest densities of dopaminergic synapses and reciprocal projections to the orbitofrontal brain regions, deficits in dopaminergic system would lead to impairments in the frontostriatal or prefrontal networks, which may lead to poorer inhibitory control, attention/working memory and decision-making (Braver and Cohen, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…We speculate that our data reflect the particular vulnerability of the PCC to HIV-induced neuroinflammation, which could have consequences for neurocognitive functioning. The prevalence of deficits in executive functioning is high in PLWH, even in those not meeting the full diagnostic criteria for HIV-NCI (Correa et al 2016). Indeed, functional neuroimaging studies have identified metabolic abnormalities in the PCC that associate with HIV infection and with progression of HIV-NCI, as well as abnormal aging and amyloid pathology in the HIV-negative population (Bladowska et al 2013;Cysique et al 2018;Murray et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cysique et al (2018Cysique et al ( , 2013 used magnetic resonance spectroscopy to detect neuronal injury (reduced N-acetyl-aspartate (NAA)) and neuroinflammation (increased myoinositol (mI)) in PCC in virally suppressed PLWH compared to HIV-negative individuals. However, we cannot attribute deficits in executive function solely to involvement of the PCC in our PLWH cohort, as such dysfunction is also affected by other brain regions, including frontal cortex and white matter, precuneus, accumbens, putamen, and globus pallidus (Correa et al 2016;Mohamed et al 2018).…”
Section: Discussionmentioning
confidence: 99%